2000
DOI: 10.1002/(sici)1521-3773(20000204)39:3<511::aid-anie511>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Al30: A Giant Aluminum Polycation

Abstract: Simple hydrothermal treatment of the well-known aluminum polycation varepsilon-Al(13) produces the novel Al(30) structure (see picture), the largest polycation yet observed. Its characterization, by X-ray diffraction and NMR spectroscopy, also solved previously unassigned signals in (27)Al NMR spectra of other Al - O species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
210
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(231 citation statements)
references
References 19 publications
13
210
0
5
Order By: Relevance
“…Dissolved (Chen et al, 2006). Al 30 has unique nanometer molecule dimension (2.0 nm in length) and eighteen positive charges (Allouche et al, 2000). However in Al 13 system, the large amount of deposited aluminum might be partly resulted from the gradual aggregation of dissolved Al 13 species.…”
Section: Aluminum Speciation Variation In Coil-pipe Testmentioning
confidence: 99%
“…Dissolved (Chen et al, 2006). Al 30 has unique nanometer molecule dimension (2.0 nm in length) and eighteen positive charges (Allouche et al, 2000). However in Al 13 system, the large amount of deposited aluminum might be partly resulted from the gradual aggregation of dissolved Al 13 species.…”
Section: Aluminum Speciation Variation In Coil-pipe Testmentioning
confidence: 99%
“…Al (Allouche et al, 2000;Rowsell and Nazar, 2000). Al 30 is more temperature resistant and less sensitive to pH variations than e-Al 13 (Allouche et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Al 30 is more temperature resistant and less sensitive to pH variations than e-Al 13 (Allouche et al, 2000). Al 30 possesses eighteen positive charges and unique nanometer molecule dimension (2.0 nm in length) (Allouche et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…So it has received the most attention (Bi et al, 2004;Gao et al, 2005 27 Al nuclear magnetic resonance (NMR) spectra about twenty years ago (Akitt and Farthing, 1981;Fu and Nazar, 1991). But its structure and stoichiometry were not determined, until 2000 it was characterized by Allouche et al (2000) and Rowsell and Nazar (2000) using X-ray diffraction and in situ 27 Al NMR. Al 30 , with 2 nm in length (Phillips et al, 2003), was the largest Al polycation that was identified in polyaluminum solution.…”
Section: Introductionmentioning
confidence: 99%